Objective Measures in Cochlear Implants. - Hughes, Michelle (Core clinical concepts in audiology., 2012)
Divided into three parts, this book covers basic science, non-physiological objective measures, and physiological measures of cochlear implants, beginning with a clear description of the underlying basic science and signal characteristics of objective measures.